In search of tris(trimethylsilylcyclopentadienyl) thorium. Issue 44 (29th October 2019) - Wedal, Justin C.; Bekoe, Samuel; Ziller, Joseph W.; Furche, Filipp; Evans, William J.
Abstract : Solution synthesis, characterization, and reactivity of a new Th(iii ) complex Cp′3 Th (Cp′ = C5 H4 SiMe3 ). Abstract : Reduction of Cp′3 ThCl, Cp′3 ThBr, and Cp′3 ThI (Cp′ = C5 H4 SiMe3 ) with potassium graphite generates dark blue solutions with reactivity and spectroscopic properties consistent with the formation of Cp′3 Th. The EPR and UV-visible spectra of the solutions are similar to those of crystallographically-characterized tris(cyclopentadienyl) Th(iii ) complexes: [C5 H3 (SiMe3 )2 ]3 Th, (C5 Me4 H)3 Th, (C5 t Bu2 H3 )3 Th, and (C5 Me5 )3 Th. Density functional theory (DFT) analysis indicates that the UV-visible spectrum is consistent with Cp′3 Th and not [Cp′3 ThBr] 1− . Although single crystals of Cp′3 Th have not been isolated, the blue solution reacts with Me3 SiCl, I2, and HCCPh to afford products expected from Cp′3 Th, namely, Cp′3 ThCl, Cp′3 ThI, and Cp′3 Th(CCPh), respectively. Reactions with MeI give mixtures of Cp′3 ThI and Cp′3 ThMe. Evidence for further reduction of the blue solutions to a Cp′-ligated Th(ii ) complex has not been observed. The crystal structures of Cp′3 ThMe and (Cp′3 Th)2 (μ-O) were also determined as part of these studies.